The Constitutional Court Adjudication and Its Implications for the Justice Seekers - Bambang Sutiyoso (Jurnal Hukum IUS QUIA IUSTUM, 2008)
The Constitutional Court adjudication, as the nature of a court decision, implies the rights that the justice seekers will appreciate. It is unfortunate, however, that the appeal procedures for those who dissatisfied with such adjudication has yet to be issued, and this may produce the disadvantages for the purpose of affording justice. For such reason, the amendment on Procedures of the Constitutional Court, particularly in the appeal procedures, is very much needed.Keyword: Adjudication, Verdict, Constitutional Court, Legal Consequence, Justice Seeker